2003
DOI: 10.1046/j.1439-0450.2003.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Field Trial with an Immunostimulating Complex (ISCOM) Vaccine against Contagious Bovine Pleuropneumonia

Abstract: The experimental field trial with an immunostimulating complex (ISCOM) vaccine has been an occasion to explore the role of a Th1 response in the pathogenesis caused by Mycoplasma mycoides subsp. mycoides small colony (MmmSC) and in immune protection. The ISCOM complex is known to promote Th1 response. Antibodies to MmmSC were detected by indirect enzyme-linked immunosorbent assay (ELISA) in the vaccinated cattle, although the levels were lower than in a previous study. No antibodies were detected by complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
0
15
0
Order By: Relevance
“…There has been little success with subunit vaccines or recombinant proteins (35), and this is especially true for CBPP, for which the only Office International des Epizootes-recommended vaccines are freeze-dried live formulations (strain T 1 44 or its streptomycin-resistant derivative T 1 SR). Research designed to produce "next-generation" vaccines (e.g., immunostimulating complex [ISCOM], capsular polysaccharide conjugate, or a whole-cell inactivated vaccine) has proceeded, although with little apparent success (2,11,28,39). It is possible that a genetic immunization approach may offer the potential for success in the field of mycoplasmal vaccines, since a successful plasmid-based whole-library immunization against Mycoplasma pulmonis was reported previously (4).…”
Section: Discussionmentioning
confidence: 99%
“…There has been little success with subunit vaccines or recombinant proteins (35), and this is especially true for CBPP, for which the only Office International des Epizootes-recommended vaccines are freeze-dried live formulations (strain T 1 44 or its streptomycin-resistant derivative T 1 SR). Research designed to produce "next-generation" vaccines (e.g., immunostimulating complex [ISCOM], capsular polysaccharide conjugate, or a whole-cell inactivated vaccine) has proceeded, although with little apparent success (2,11,28,39). It is possible that a genetic immunization approach may offer the potential for success in the field of mycoplasmal vaccines, since a successful plasmid-based whole-library immunization against Mycoplasma pulmonis was reported previously (4).…”
Section: Discussionmentioning
confidence: 99%
“…This disadvantage was considered for the introduction of agar to replace minced lung supernatant in the inoculum. Agar was previously used as an adjuvant in M. mycoides vaccine preparations (Piercy and Knight 1957) and has been used successfully on donor animals in several trials, inoculated in combination with pure MmmSC cultures and saline Wesonga and Thiaucourt 2000;Huebschle et al 2003Huebschle et al , 2006Dedieu et al 2005;Jores et al 2008). Observations in these trials suggested that the disease reproduced through this method was similar to that reproduced through contact transmission.…”
Section: Introductionmentioning
confidence: 99%
“…VOL. 17,2010 PROTEIN-SPECIFIC ANALYSIS OF CBPP VACCINE TRIAL 859 depending on the cutoff for signal differences between the groups. The criterion of a 3-fold-higher signal in T1/44-vaccinated cattle was imposed in recognition of the small sample set of five cattle per group to reduce the impact of individual animals and to isolate proteins with the comparably largest increase in IgG titers.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the formulation have been suggested to easily improve the live vaccines (22), but most recent work has been done to find completely new vaccine formulas. Trials with a saponin-inactivated whole-cell antigen (27) and immunostimulating complex (ISCOM) formulations from the whole mycoplasma cell membrane (2,17) have so far been unsuccessful. Two subunit vaccine candidates have been evaluated: the first based on the capsular polysaccharide of M. mycoides SC (36) and the second based on the immunogenic lipoprotein LppQ (27).…”
mentioning
confidence: 99%